Combined effects of temperature, salinity, and diet simulating upwelling and nonupwelling seasons alter life‐history characteristics of a tropical invertebrate. Issue 24 (12th December 2019) - Camargo‐Cely, Alejandra; Collin, Rachel
Abstract: Upwelling is known to affect the ecology and life history of temperate nearshore organisms, and these effects are thought to be mediated by changes in temperature and food supply. However, little information is available for tropical systems. To understand how changes in the intensity of upwelling might impact marine invertebrates, we tested how factorial combinations of temperature, salinity, and phytoplankton availability affected growth and reproduction of a common intertidal snail, Crepidula cf. marginalis . We used temperatures typical of nonupwelling (29°C), moderate (26°C) and severe (23°C) upwelling, salinities typical of nonupwelling (30 ppt) and upwelling (34 ppt) and a good diet ( Isochrysis ) and a better diet ( Isochrysis and Tetraselmis ) as a proxy for increased productivity during upwelling. Overall, temperature and diet had consistent effects on body size, with better food and lower temperatures promoting larger size, as well as promoting shorter time to first reproduction. Diet had the largest effects on clutch size, with clutch size increasing with better diet. Temperature had the largest effect on offspring size and the frequency of discarded broods; offspring size decreased with increasing temperature and the frequency of discarded broods also decreased with increasing temperatures. We found no significant 3rd order interactions and few significant strong 2nd order interactions, which have often been found in similar experimental studies using stressful treatments. For this tropical slipper limpet, the effect of higher food and cooler temperatures during upwelling appears to be positive, promoting higher growth rates, larger clutch sizes, and larger offspring size suggesting that both factors likely play an important role underlying reproductive responses to upwelling. Climatic changes, like El Niño, which suppress upwelling in the Bay of Panama, appear likely to negatively impact this species. Abstract : To understand how they interact to effect life histories, we raised tropical snails ( Crepidula cf. marginalis ) under a factorial combination of diet, temperature, and salinity. The results show that a combination of lower temperatures and higher food availability results in increased growth, larger broods, and larger hatching sizes. C . cf. marginalis, therefore, performs better under conditions similar to upwelling compared to those similar to nonupwelling conditions experienced in the Bay of Panama. This effect is largely mediated through the increased body size under higher food and cooler temperatures.